Impact of sleep apnea syndrome on survival in patients with multiple system atrophy. (February 2017) - Flabeau, Olivier; Ghorayeb, Imad; Perez, Paul; Maillard, Aline; Taillard, Jacques; Philip, Pierre; Foubert-Samier, Alexandra; Tison, François; Meissner, Wassilios G.
Abstract: Introduction: Sleep apnea is very frequent in multiple system atrophy (MSA) and may contribute to the poor prognosis. The aim of the present study was to prospectively assess the relation between sleep apnea and survival in 30 consecutive MSA patients recruited at the French Reference Center for MSA. Methods: Patients with "probable" MSA according to current consensus diagnosis criteria were enrolled in this prospective cohort study. All patients received full polysomnography at baseline and were then followed for up to 4.5 years. The prognostic role of sleep apnea was assessed by a Cox model in an univariate analysis and then adjusted on other potential factors. Results: Analyzable polysomnographic recordings were available for 28 patients. Sleep apnea was found in 11 patients. During follow-up, 15 patients died, including 9 with baseline sleep apnea. In an univariate analysis, sleep apnea, Unified MSA Rating Scale I + II score at baseline and at year one, and disease duration were associated with mortality. However, when adjusting for disease duration and baseline Unified MSA Rating Scale score, the association between sleep apnea and mortality was no longer significant. Conclusions: Sleep apnea was not an independent factor associated with mortality in this prospective cohort study. Highlights: Sleep apnea is very frequent in multiple system atrophy (MSA). We assessed the relation between sleep apnea and survival in 30 MSA patients. Sleep apnea was not an independent factor associated with mortality in our prospective cohort.